The interactions between extracellular vesicles and mesenchymal stem cells: Their potential roles in osteoarthritis development and cartilage repair - Qiong Yang; Danyang Yue; Qian Ren; Guoqing Xia; Baihui Zhang; Yinyin Qin; Tianfei Ran; Min Wang; Li Pei; Jun Pan (Extracellular Vesicle)
Osteoarthritis (OA) is a chronic cartilage degeneration disease affecting total joint and with a wide global impact. Stem cell therapy has emerged as a potential stock for the treatment of OA. Exosomes are the mainstay of the paracrine function in stem cells, acting as an important mediator of intercellular communication. The purpose of this review is to sort out the close relationships among OA, MSCs, and exosomes. We find though majority of researches on exosomes focus on normal MSC-derived exosomes to restore tissues, studies demonstrate that OA or inflammation-induced microenvironment can alter exosomes, which in turn affect the biological behaviors and functions of receptor cells in the joint cavity, including proliferation and differentiation of MSCs. Exosomes, MSCs and OA form a triangular relationship. More future research directions are exploring the effects of OA-derived exosomes on chondrogenic differentiation of MSCs, especially on mitochondria to disclose the reasons for failure endogenous repair by MSCs, and normalizing the OA exosomes to treat OA.